Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Akuisisi: Studi pada Perusahaan yang Diakuisisi di Bursa Efek Indonesia Tahun 2025 - Yosep Eka Putra; Miftahur Rahmah; Putri Khairul Nisa; Liana Putri Nabila; Putri Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Acquisition is one of the external growth strategies aimed at improving efficiency, expanding market share, and strengthening corporate performance. However, the implementation of acquisitions does not always lead to immediate improvements in financial performance. This study aims to analyze the comparison of financial performance before and after acquisitions among companies listed on the Indonesia Stock Exchange (IDX) in 2025. The research employs a descriptive quantitative method using secondary data obtained from the companies’ annual financial statements for the 2024-2025 period. The sample consists of 10 companies selected through purposive sampling. The analysis was conducted by comparing profitability, liquidity, solvency, and activity ratios. The findings indicate that most companies experienced a decline in profitability and activity ratios during the first year following the acquisition. This condition suggests that the post-acquisition integration process requires time before optimal economic benefits can be realized. On the other hand, the increase in liquidity ratios among the majority of companies reflects an improvement in their ability to meet short-term obligations. Meanwhile, changes in solvency ratios varied according to the financial conditions of each company. These findings confirm that the impact of acquisitions on financial performance tends to be more evident in the long term rather than in the short term.